Optimization research on the inlet and outlet passage of shaft tubular pump based on CFD - Yi Miao; Yuanfeng Hao; Nianping Shi; Liang Peng (AIP Advances)
To address the problems of low operational efficiency and high hydraulic loss in the vertical shaft tubular pump device at the Taiziwei Port Lock Station, an optimization method for the inlet and outlet flow passages based on numerical simulation is proposed. The Reynolds-averaged Navier–Stokes equations, combined with a rotating turbulence model, are used to conduct three-dimensional modeling and flow analysis of the pump device. With refined adaptive mesh generation, multiple optimization schemes for the inlet contour and outlet diffusion section are designed and compared. The verification results show that under the initial design conditions, the pump efficiency increases from 72.37% to 74.30% and reaches 77.18% under optimal operating conditions. The results indicate that the optimized pump device can effectively reduce energy loss and improve the flow state. The proposed optimization scheme provides a systematic design approach and practical reference for energy-saving improvements in low-head pumping systems, demonstrating strong engineering applicability.